2021
DOI: 10.1039/d1na00120e
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical preparation of polymer–metal nanocomposites with catalytic and plasmonic properties

Abstract: Polymer-metal nanocomposites are of increasing interest for a wide range of applications; however, the preparation of these nanocomposites often requires the addition of external initiation and reducing agents for the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 49 publications
(64 reference statements)
0
31
0
2
Order By: Relevance
“…Ultrasound has been used to initiate the PISA process without the addition of exogenous chemical initiators. 57 The versatility of ultrasound is also demonstrated by its ability to generate reducing species to form metal nanoparticles without the addition of reductant. In this study, PEG- b -PDMAEMA-TTC macro-RAFT agent was first synthesized, and then used to mediate dispersion polymerization of HPMA in water under sonication at room temperature.…”
Section: Hybrid Materials Synthesized Via Pisamentioning
confidence: 99%
See 3 more Smart Citations
“…Ultrasound has been used to initiate the PISA process without the addition of exogenous chemical initiators. 57 The versatility of ultrasound is also demonstrated by its ability to generate reducing species to form metal nanoparticles without the addition of reductant. In this study, PEG- b -PDMAEMA-TTC macro-RAFT agent was first synthesized, and then used to mediate dispersion polymerization of HPMA in water under sonication at room temperature.…”
Section: Hybrid Materials Synthesized Via Pisamentioning
confidence: 99%
“…The most common applications for polymeric nanoparticles including those prepared by the PISA process, is drug delivery and other biomedical applications. Besides, PISA-prepared nano-objects have been explored as catalysts, 56–60 Pickering emulsifiers, 22,61–64 imaging agents, 65,66 lubricants, 67 templating agents, 68–70 pigments, 54,55 etc. The following section summarizes some applications of PISA-prepared nano-objects.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polymerization-induced self-assembly (PISA) has been exploited as a robust and scalable technique for the preparation of diblock copolymers nanomaterials with different morphologies at high solid contents (up to 40–50 wt %). More importantly, the PISA technique can achieve the chemical synthesis and self-assembly in one step without further purification, especially for those prepared in the aqueous environment. However, it has been demonstrated that the utilization of PISA for the fabrication of complex patchy particles composed of triblock terpolymers was extremely challenging in the aqueous medium, mainly because of the limited monomers that are suitable for this process. , The existing examples all require the utilization of PISA-suitable monomers, which are soluble in water, whereas the formed polymer should be hydrophobic for in situ self-assembly. , Water-immiscible monomers like styrene and tert -butyl acrylate commonly generate kinetically trapped spheres.…”
mentioning
confidence: 99%